2016
DOI: 10.1016/j.ygyno.2016.04.179
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 10-year survivors of high-grade serous ovarian carcinoma

Abstract: Objective-High-grade serous carcinoma (HGSC) generally presents at an advanced stage with poor long-term (LT) survival. Here we describe clinical features found in women surviving HGSC for ten or more years.Methods-A multi-center research consortium was established between five participating academic centers. Patient selection criteria included high-grade serous ovarian, fallopian tube, or peritoneal carcinoma with at least ten years of follow up. Non-serous, borderline tumors and lowgrade serous subtypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 13 publications
(15 reference statements)
3
36
0
Order By: Relevance
“…This, in conjunction with data showing worse outcomes for high‐grade serous tumors compared to other types, suggests that some tumors may be intrinsically more aggressive than others. While differences in survival across tumor subtypes can be explained, in part, by surgical outcomes, a recent study noted that changes in chemotherapy regimens did not substantially influence long‐term survival . More recently, studies have shown that exposures before diagnosis are differently associated with ovarian cancer subtypes, with each histologic type showing a distinct pattern of risk factor associations .…”
Section: Introductionmentioning
confidence: 99%
“…This, in conjunction with data showing worse outcomes for high‐grade serous tumors compared to other types, suggests that some tumors may be intrinsically more aggressive than others. While differences in survival across tumor subtypes can be explained, in part, by surgical outcomes, a recent study noted that changes in chemotherapy regimens did not substantially influence long‐term survival . More recently, studies have shown that exposures before diagnosis are differently associated with ovarian cancer subtypes, with each histologic type showing a distinct pattern of risk factor associations .…”
Section: Introductionmentioning
confidence: 99%
“…Dao et al ., in a multi‐centre study, described 203 patients with HGSC who survived more than 10 years, 72.4% of whom had FIGO IIIc disease initially. Eighty‐eight patients (46.8%) remained recurrence‐free after a median follow‐up of 144 months . A study of the California Cancer Registry on 11 541 ovarian cancer patients among all histological subtypes and stages identified a total of 3583 patients (31%) who survived more than 10 years and, of these, 32.4% had stage III/IV disease.…”
Section: Introductionmentioning
confidence: 99%
“…HGSCs are generally symptomatic and present at an advanced stage, and only 2% of HGSC cases are diagnosed at FIGO Stage I. In patients with advanced disease, the most important predictor of survival is complete surgical resection of all visible disease.…”
Section: Introductionmentioning
confidence: 99%